Analysis of Visual Function in Patients with Nuclear, Cortical and Posterior Subcapsular Cataracts in Lumbini Eye Institute and Research Center - Khati, Sambandha; Gautam, Anisha; Bhusal, Usha; Thapa, Nisha Rana; Thapa, Saraswati Khadka (Journal of Bharatpur Hospital, 2025)
Background Cataract is the leading cause of reversible blindness worldwide, affecting visual function through different morphological types. Nuclear sclerosis often reduces distance vision with myopic shift, cortical cataract commonly causes glare and variable acuity, while posterior subcapsular cataract disproportionately impairs best-corrected visual acuity. Evaluating these differences in visual function is important for patient counseling and surgical planning. This study analyzes visual acuity, contrast sensitivity, color vision and glare among patients with nuclear, cortical, and posterior subcapsular cataracts. Methods A cross-sectional study was conducted among 395 patients (131 per cataract type) at Lumbini Eye Institute, Nepal. Cataract grade was assessed using LOCS III, and visual function evaluated with Snellen’s chart (VA), Ishihara chart (color vision), Pelli-Robson chart (contrast sensitivity), and Glare and Halo Questionnaire. Results Among 395 patients (52.2% female), mean logUCVA was worst in nuclear sclerosis (0.94±0.35) and best in cortical cataract (0.76±0.33; p-value<0.001), while logBCVA was poorest in PSCC (0.61±0.31; p-value< 0.001). NS showed myopic, CC hyperopic, and CC had highest astigmatism (p-value=0.008). Contrast sensitivity was highest in CC and lowest in PSCC (p-value=0.015). Glare increased with cataract grade, most frequent in PSCC (92%). Color vision remained normal in >96% of all groups (p-value=0.66). Conclusions Visual function varied among cataract types, with nuclear sclerosis showing worse UCVA, posterior subcapsular cataract worse BCVA, cortical cataract higher contrast sensitivity, and glare increasing with cataract grade, while color vision remained largely unaffected.